Utilization of CO2 for production of aromatics via ZnO/ZrO2-ZSM-5 tandem catalyst. (Journal of Architectural Design, 2024)
CO2 Hydrogenation to Aromatics Tandem Catalyst Methanol Synthesis in Oxides AreneBased Cyclization Over the past decades, great progress has been made in CO2 hydrogenation to a variety of C1 chemicals, lower olefins, and gasoline. However, due to the extreme inertness and high aromatization barrier of CO2, the synthesis of aromatics from one-shot CO2 hydrogenation is still a major challenge. Here, we present a tandem catalyst consisting of ZnO/ZrO2 and ZSM-5 zeolite for one-shot conversion of CO2 to aromatics with 70% selectivity, and the selectivity of incoming methane is suppressed to below 1%. The path of CO2 → CH3OH → aromatics over the tandem catalyst was demonstrated.